Solusi Tepat Mengatasi Kesalahan Pemasangan Grounding pada kWh Meter di Cluster Natura Bekasi, Jawa Barat - Djoni, Djoni; Abrianto, Heru; Gultom, Arlewes (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyzes the suitability of the earthing system of household electrical installations in the Natura Cluster, Bekasi, with the PUIL 2011 standard, considering that the increase in power and degradation of old installations increase the risk. A qualitative approach with data triangulation (measurement, observation, documentation study) was used. The results of earthing resistance measurements with a Digital Earth Tester showed values above the PUIL 2000 standard (<5 Ω) at a depth of 50 cm (average 13.17 Ω) due to the soil structure. However, at a depth of 300 cm, an average value of 0.03 Ω was obtained, meeting the standard. This indicates that the cluster kWh installation meets the feasibility standard at the optimum depth. This study recommends a review of the earthing system, including planting depth, understanding soil characteristics, periodic maintenance. Also, system reassessment, and grounding cable insulator coating. This is intended to improve the safety and reliability of the residential electrical system.